Intonation Difference Between Chinese EFL Speaker and Indonesian EFL Speaker : An Acoustic Features Analysis - Cut Nadia Muji Rahmah; Aisyah Inka Putri Lubis; Tengku Syarfina; Rahmadsyah Rangkuti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Intonation is one of the acoustic features that is highly emphasised by English learners worldwide, including Chinese EFL and Indonesian EFL speakers. The primary focus of the research is to compare variations in intonation between Chinese EFL and Indonesian EFL speakers while at the same time observing the other two acoustic features, which are intensity and duration. To make this research more comprehensive, a native English speaker’s pronunciation was also included to set the standard of English pronunciation. The data was visualised using the phonetic software PRAAT following the experiment. The findings indicate that Indonesian EFL speakers exhibit intonation patterns more similar to native English speakers compared to Chinese EFL speakers, although the specific intonation differences from native speakers remain evident. Learning about phonetic theory and adjusting intonation with the help of visual phonetic software are both effective ways to address this issue.